Efektivitas Pelaksanaan Kegiatan Keagamaan pada Masa Pandemi Covid-19 Di Gampong Tutong, Labuhanhaji Barat, Aceh Selatan - Nabila, Elsa; Fakhruddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This study aims to describe how effective the implementation of religious activities is in the midst of pandemic COVID-19 in Tutong Village. This research is a descriptive qualitative research. The research subject is the Ustadz or Ustadzah in recitation at the children's recitation place. Ustadz the leader of the weekly Islamic study, as well as several people who take part in the weekly study. The research instrument used interview, observation and documentation techniques. The result showed that religious activities carried out in the midst of pandemic were effective, both in the implementation of routine assesment and children's recitation. There are no obstacles in the implementation of the two activities, and there is also noregulation requiring all participants who participate in recitation to wear masks, but in children recitation place, student are required to maintain personal hygienie. As for the two religious activities, the Ustdaz or Ustadzah always provide education about COVID-19 to children's recitation student and to routine recitation participants every week.